Private actors as participants in international law : a critical analysis of membership under the Law of the Sea - Rocha, Armando Luis Silva (London, England : Zed Books, 2021)
"This book examines the status of private actors as subjects of law under the rules of the international law of the sea. Providing a methodology for the notion of a single legal personality, it provides a clear understanding of membership in international law in order to establish to what extent private actors can be rights-holders or duty-bearers. It does this by taking a theoretical perspective which allows the reader to interpret their relevance in international law. This unique and innovative work makes a significant contribution to the current scholarly debates on private actors in international law"--
Introduction -- Participation of private actors as subjects of law -- Unveiling private actors' entitlements -- The narrow reading of explicit private actors' entitlements -- Taking systemic interpretation seriously -- Conclusion.
Based on author's thesis (doctoral - Universidade Católica Portuguesa, 2018) issued under title: Private actors as rights-holders under the international law of the sea.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Non-state actors (International relations); Law of the sea; Law of the sea; Electronic books